2022
DOI: 10.1002/adma.202204132
|View full text |Cite
|
Sign up to set email alerts
|

Suppressing Charged Cation Antisites via Se Vapor Annealing Enables p‐Type Dopability in AgBiSe2–SnSe Thermoelectrics

Abstract: figure-of-merit (zT) of a TE material, which is given by zT = S 2 σT/κ, where S, σ, T, and κ are the Seebeck coefficient, electrical conductivity, absolute temperature, and thermal conductivity, respectively. [3] Nevertheless, the competing interplay between electrical and thermal properties has stagnated the rise of zT for decades. [4] Ternary ABX 2 -type (A = group I, B = group V, X = group VI elements) compounds have gained considerable attention as promising candidates for TE applications. [5] Lone-pair el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 92 publications
0
6
0
Order By: Relevance
“…The minimum value of the lattice thermal conductivity, observed at 623 K, followed by a conspicuous increase ( Figure 5 ) can be explained, based on the effect of the atomic ordering happening at that temperature. It has been reported that this atomic ordering effect can be inferred from the unconventional temperature dependence of the transport properties [ 30 ], such as in the lattice thermal conductivity, as well as in the resistivity, the Seebeck coefficient and the weighted mobility.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The minimum value of the lattice thermal conductivity, observed at 623 K, followed by a conspicuous increase ( Figure 5 ) can be explained, based on the effect of the atomic ordering happening at that temperature. It has been reported that this atomic ordering effect can be inferred from the unconventional temperature dependence of the transport properties [ 30 ], such as in the lattice thermal conductivity, as well as in the resistivity, the Seebeck coefficient and the weighted mobility.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, the precise determination of the Ag/Sb occupancy in this telluride has a significant relevance in terms of transport properties. This cation disordering is often found in other ternary cubic chalcogenide compounds, with the associated point defects usually leading to a poor reproducibility of the properties of these materials [ 30 ]. Recently, Roychowdhury et al have proven that the atomic ordering can be achieved in AgSbTe 2 with cadmium (Cd) doping [ 31 ].…”
Section: Introductionmentioning
confidence: 99%
“…In parallel, considering the positive role of Sn, Ag, and Bi in reducing the lattice thermal conductivity value of Cu 2 Se, as well as the potential advantages of stepwise alloying engineering, (SnSe) 1– x (AgBiSe 2 ) x was selected as the dopant for alloying. Furthermore, the stable existence of high-pressure cubic rock salt phase SnSe can be promoted by adjusting the x content in (SnSe) 1– x (AgBiSe 2 ) x . , The large degenerate number caused by the highly symmetric structure in cubic (SnSe) 0.75 (AgBiSe 2 ) 0.25 is beneficial to the improvement of Seebeck coefficient. Inherently low thermal conductivity (SnSe) 0.75 (AgBiSe 2 ) 0.25 was used as an additive to combine these effects to optimize the thermoelectric properties of Cu 1.9 Se.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the stable existence of high-pressure cubic rock salt phase SnSe can be promoted by adjusting the x content in (SnSe) 1−x (AgBiSe 2 ) x . 23,24 The large degenerate number caused by the highly symmetric structure in cubic (SnSe) 0.75 (AgBiSe 2 ) 0.25 is beneficial to the improvement of Seebeck coefficient. Inherently low thermal conductivity (SnSe) 0.75 (AgBiSe 2 ) 0.25 was used as an additive to combine these effects to optimize the thermoelectric properties of Cu 1.9 Se.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Native defects often regulate electron-hole recombination mechanisms in, e.g., photovoltaics, [1][2][3][4][5] whereas electrical and thermal transport properties can be tuned by controlling point defects and the resulting carrier concentrations in, e.g., thermoelectrics. [6][7][8][9][10][11][12][13][14] The phase stability, defect formation energies, and carrier concentrations are interconnected properties of a semiconductor that are influenced by the thermodynamic environment. 15,16 In particular, a thermodynamic state is defined by a fixed set of elemental chemical potentials that are determined by the impurity phases with which a material is in equilibrium.…”
Section: Introductionmentioning
confidence: 99%